Caracterização físico-química, atividade antioxidante e perfil de compostos fenólicos em vinhos de inverno produzidos e comercializados no sul de Minas Gerais - Vilas Boas, Ana Carolina (2016)
The physical-chemical characteristics and bioactive compounds contents of fine wines are influenced by climatic conditions and the grape cultivar used. Thus, the aim of this study was to perform the physical-chemical characterization, evaluation of the antioxidant activity and the phenolic compounds profile of different red wines produced in the South of Minas Gerais State, Brazil. Red wines of the varieties Merlot, Syrah, Cabernet Sauvignon and Cabernet Franc; White wines of the varieties Sauvignon Blanc and Chardonnay; Rose wines of the Syrah variety were produced in the respective wineries located in the south of Minas Gerais State and after bottling were taken to the Postharvest Laboratory of the Federal University of Lavras. Physical-chemical analyses, color analysis, total phenolic content and profile of the phenolic compounds, anthocyanins content and antioxidant activity were carried out aiming the characterization fine wines of the southern region of the state. Fine wines produced in Minas Gerais State demonstrated interesting physical-chemical characteristics, but some red wines still have alcohol content above the legislation limit, however white and rosé wines are in accordance to the limits established by legislation regarding alcoholic content, total acidity, volatile acidity and SO2 content. Wines of the studied region presented higher amounts of t-resveratrol when compared to wines produced in traditional regions of the country. The wines studied presented significant contents of total phenolics, anthocyanins, flavonol, flavanols and phenolic acids, with the necessary bioactive characteristics to act as functional food for consumers and to allow the competition with traditional wine production regions and the consolidation of wines produced in the south of Minas Gerais State.